1998
DOI: 10.1007/s11661-998-0319-3
|View full text |Cite
|
Sign up to set email alerts
|

Solidification of Nb-bearing superalloys: Part I. Reaction sequences

Abstract: The solidification reaction sequences of experimental superalloys containing systematic variations in Fe, Nb, Si, and C were studied using differential thermal analysis (DTA) and microstructural characterization techniques. The reaction sequences responsible for microstructural development were found to be similar to those expected in the Ni-Nb-C ternary system and commercial superalloys of comparable composition. The solute-rich interdendritic liquid generally exhibited two eutectic-type reactions at the term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(82 citation statements)
references
References 14 publications
7
74
0
1
Order By: Relevance
“…O padrão de difração de área selecionada deste precipitado é apresentado na Figura 11b, o qual foi caracterizado inequivocamente como sendo fase Laves. Foram observadas ainda grandes colônias de fases secundárias com morfologia eutética lamelar rica em Nb, bem como longas cadeias de estruturas eutéticas ao longo das regiões interdendríticas e intercelulares, como pode ser observado na De fato, a morfologia destes eutéticos assemelha-se a algumas formações eutéticas observadas nos trabalhos de Dupont et al [38,39] e Cieslak et al [40], a qual foi considerada pelos autores característica de fase Laves rica em Nb. As informações obtidas até então são consistentes com os resultados reportados na literatura.…”
Section: Microestrutura Da Zona Fundidaunclassified
“…O padrão de difração de área selecionada deste precipitado é apresentado na Figura 11b, o qual foi caracterizado inequivocamente como sendo fase Laves. Foram observadas ainda grandes colônias de fases secundárias com morfologia eutética lamelar rica em Nb, bem como longas cadeias de estruturas eutéticas ao longo das regiões interdendríticas e intercelulares, como pode ser observado na De fato, a morfologia destes eutéticos assemelha-se a algumas formações eutéticas observadas nos trabalhos de Dupont et al [38,39] e Cieslak et al [40], a qual foi considerada pelos autores característica de fase Laves rica em Nb. As informações obtidas até então são consistentes com os resultados reportados na literatura.…”
Section: Microestrutura Da Zona Fundidaunclassified
“…Laves phases and Nb-carbides NbC are known to form in eutectic reactions. The systematic study by DuPont et al [141][142][143], spanning from DTAexperiments and microsegregation analysis of fusion welded samples to modeling microsegregation and phase formation along the solidification path of various alloys, highlights the major role played by carbon.…”
Section: The Solidification Path and Microstructure Formationmentioning
confidence: 99%
“…[2,8] The results of the quantitative analysis of the chemical composition (SEM/EDS) of precipitates are presented in Table 4. For comparison, this table also includes the chemical composition of the Laves phase in weld overlays examined by Cieslak [8], Floren [18] and DuPont [19]. This analysis showed that the elongated phase was enriched in Mo and Nb, and simultaneously it contained low amounts of such elements as Ni, Cr and Fe that do not segregate to interdendritic areas.…”
Section: Resultsmentioning
confidence: 99%